2011
DOI: 10.1159/000328789
|View full text |Cite
|
Sign up to set email alerts
|

Association between Maternal Allergic Rhinitis and Asthma on the Prevalence of Atopic Disease in Offspring

Abstract: Background: Asthma is a common co-morbidity of allergic rhinitis (AR). The prevalence of these two allergic diseases has increased in China and has been shown to cluster in families independently. This study evaluated the association between maternal AR (presenting with or without asthma) and the allergic conditions in offspring. Methods: Women (n = 592) diagnosed with AR were recruited for this study; 379 patients presented with AR and 213 presented with both AR and asthma. Total serum IgE levels and nasal eo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 83 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…The importance of parental rhinitis as a risk factor for allergic rhinitis in their offspring is well understood [13,14], and the results of our study further emphasize this relationship. Children with at least one parent who suffered from allergic rhinitis were more likely to have the disease themselves.…”
Section: Discussionsupporting
confidence: 71%
“…The importance of parental rhinitis as a risk factor for allergic rhinitis in their offspring is well understood [13,14], and the results of our study further emphasize this relationship. Children with at least one parent who suffered from allergic rhinitis were more likely to have the disease themselves.…”
Section: Discussionsupporting
confidence: 71%
“…A more recent study also found that maternal asthma and allergic rhinitis were associated with increased risk of their offspring developing allergic conditions. 12 Residential proximity to busy roads was associated with respiratory symptoms. 13 , 14 As shown in Table 4, the prevalence of respiratory morbidity increased with increasing proximity of a child’s home to traffic.…”
Section: Discussionmentioning
confidence: 99%
“…Traherne et al [34] showed that a polymorphism of the high-affinity IgE receptor beta-chain (FceRI-ß) was strongly associated with positive skin prick test results and greater allergen-specific IgE levels when inherited from mothers. The severity of maternal allergic rhinitis, asthma comorbidity, elevated serum IgE levels, and nasal eosinophilia were all associated with an increased risk of offspring developing [35]. On the other hand, Sunyer et al [36] evaluated mothers and their children from the Asthma Multi-centre Infants Cohort Study (AMICS), with the aim of examining the effects of pre-and postnatal environmental exposure in the inception of atopy and asthma.…”
Section: Atopymentioning
confidence: 99%